2014
DOI: 10.1007/s12307-014-0150-x
|View full text |Cite
|
Sign up to set email alerts
|

Stroma as an Active Player in the Development of the Tumor Microenvironment

Abstract: The stroma is a considerable part of the tumor microenvironment. Because of its complexity, it can influence both cancer and immune cells in their behavior and cross-talk. Aside from soluble products released by non-cancer and cancer cells, extracellular matrix components have been increasingly recognized as more than just minor players in the constitution, development and regulation of the tumor microenvironment. The variations in the connective scaffold architecture, induced by transforming growth factor bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
44
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(46 citation statements)
references
References 92 publications
0
44
0
Order By: Relevance
“…Our results also point out that blood vessels are crucial to the spatial location and temporal migration of the EMT cells, suggesting that targeting blood vessel related factors might be beneficial in impeding EMT occurrence and restraining EMT cells’ behaviors. Blood vessels supply nutrients and growth factors that allow tumors to grow (22). A panel of growth factors, including TGF-β, EGF, FGF, hepatocyte growth factor (HGF), Insulin-like growth factor 1 (IGF-1), and platelet-derived growth factor (PDGF), was investigated in inducing the EMT-like morphological changes of the PyMT tumor-derived EMT cells; of these TGF-β and HGF provoked obvious loss of cell-cell contacts, which was not observed with other growth factors (16).…”
Section: Resultsmentioning
confidence: 99%
“…Our results also point out that blood vessels are crucial to the spatial location and temporal migration of the EMT cells, suggesting that targeting blood vessel related factors might be beneficial in impeding EMT occurrence and restraining EMT cells’ behaviors. Blood vessels supply nutrients and growth factors that allow tumors to grow (22). A panel of growth factors, including TGF-β, EGF, FGF, hepatocyte growth factor (HGF), Insulin-like growth factor 1 (IGF-1), and platelet-derived growth factor (PDGF), was investigated in inducing the EMT-like morphological changes of the PyMT tumor-derived EMT cells; of these TGF-β and HGF provoked obvious loss of cell-cell contacts, which was not observed with other growth factors (16).…”
Section: Resultsmentioning
confidence: 99%
“…31,32 Pathological images harbor essential information on the histological organization and morphological characteristics of tumor cells and their surrounding tumor microenvironment, both of which affect tumor growth patterns and contribute to tumor prognosis. 33 However, this information is hard to distinguish and extract using only the human eye and brain. Therefore, systematic analyses of pathological images using computer algorithms could reveal hidden information in decoding tumor development and progression in lung cancer.…”
Section: Discussionmentioning
confidence: 99%
“…A heterogeneous population of stromal cells surround the tumor cells and their microenvironment . Fibroblasts, immune/inflammatory cells, endothelial or mesenchymal cells, adipocytes, and bone marrow‐derived stem cells reside in the tumor microenvironment, are embedded in an extracellular matrix (ECM), and are nourished by a vascular network . In addition to the confirmed role in the tumor initiation, progression, and metastasis, stromal cells are emerging as new research targets in the MDR field .…”
Section: Introductionmentioning
confidence: 99%
“…[9] Fibroblasts, immune/inflammatory cells, endothelial or mesenchymal cells, adipocytes, and bone marrow-derived stem cells reside in the tumor microenvironment, are embedded in an extracellular matrix (ECM), and are nourished by a vascular network. [10] In addition to the confirmed role in the tumor initiation, progression, and metastasis, stromal cells are emerging as new research targets in the MDR field. [11] It has been reported that the organization of stromal cells and the composition of ECM are involved in the generation of a significant drug concentration gradient, metabolic changes, and increased interstitial fluid pressure, all of which can significantly enhance the resistance of tumor cells to chemotherapeutics.…”
mentioning
confidence: 99%